Efeitos de dois programas de exercício físico sobre o controle postural e a dor lombar em policiais militares: Pilates x exercícios isométricos - Tavares, Janny Mírian Antonelli (2019)
The police activity and the use of personal protective equipment point to a predisposition to the onset of low back pain in this professional category, affecting the muscular functions, causing limitations and functional incapacity. The objective of the present study was to identify the effect of two exercise programs, Pilates and Isometric on neuromuscular parameters and reduction of low back pain in military police. Participating in the study were 34 military policemen from the city of Curitiba-PR, aged 21-45 years, thus forming the Pilates (GP = 12), Isometric (GI = 12) and control group (GC = 10). Pilates solo sessions and Isometric Exercises were applied twice weekly for 3 months (24 sessions). In order to compare the effects of the two training programs, the changes in the electrical activation (recruitment) of the flexor and extensor muscles of the trunk and the intensity of the low back pain were quantified by performing the following tests: a) strength test or torque peak (PT) of the trunk flexor and extensor muscles; b) isometric resistance test of the flexors (RIFT) and extensors (RIET) of the trunk; c) and extensor muscles of the trunk and hip to quantify the level of muscle activation (RMS); d) postural control test during (RMS) onset of muscle activation (AMI); e) application of the Visual Analog Pain Scale (EVA) and the disability questionnaire (QIRM). The data were submitted to a standard descriptive analysis (mean and standard deviation) and normality and homogeneity by the Levene and Shapiro Wilk test. In order to verify the influence of the Pilates and Isometric exercise programs on the variables mentioned in the PRE and POS conditions in the 3 GP, GI and GC groups, a two way ANOVA was applied for repeated measurements. The Bonferroni test was used to identify where statistical differences occurred. Pearson's Chi-square correlation test (χ2) was used to identify the effects of the variables analyzed in the study on pain intensity. Statistical tests were performed in the Statistical software version 5.5 and the variables were tested with a significance level of p<0.05. Both groups (GP and GI) improved their performance on the strength and resistance of trunk flexors and extensors compared to pre-training and CG. The muscle activation level (RMS) during the MVIC also increased for the RA and EL muscles in the GP and GI groups when compared to the pre-training and the GC andthe muscle activation sequence, observed through the latency time during the test altered compared to pre-training and CG, both for GP and GI. The intensity of the low back pain presented a 73% reduction provided by the two exercise programs in a similar way compared to the pre-training and the CG. Therefore, both the Pilates and the Isometric programs were efficient in reducing pain, strength gains and isometric resistance and capable of modifying muscle coordination, activation level and anticipatory timing of trunk stabilizers in military police.